ROBLOX AS OPEN TEXT: IDENTITY, MEANING, AND IDEOLOGY THROUGH ECO’S SEMIOTICS - Rustandi, Yuyus; Sutisna, Nanang (Paradigma: Jurnal Kajian Budaya, 2025)
This study examines Roblox as a digital cultural space that constructs and represents adolescent identity through Umberto Eco's semiotic approach. Roblox functions not only as a game platform but also as an open text comprising visual signs, social symbols, and complex narratives. This studi is based on a literature review from nine prior empirical studies, this research analyzes how avatars, virtual environments, Robux economy, and user communities shape diverse systems of meaning. Findings show that Roblox serves as a site for identity construction, simulation of social values, and reproduction of dominant discourses such as capitalism and gender performance. The study concludes that Roblox opens up possibilities for symbolic awareness and digital literacy education through participatory experiences. It underscores the importance of semiotic literacy to navigate today's complex and evolving digital culture.